“Pemalang pusere Jawa”: Model City Branding dalam Mempromosikan Destinasi Wisata Kabupaten Pemalang, Jawa Tengah, Indonesia: “Pemalang pusere Jawa“: A City Branding Model in Promoting Tourism Destination of Pemalang Regency, Central Java, Indonesia - Riska Rahayu; Achmad Nurmandi; Salahudin Salahudin; Dian Suluh Kusuma Dewi (Society, 2020)
This research aims to analyze the City Branding model “Pemalang pusere Jawa” in Pemalang Regency, which focuses on the strategy of the Government to develop a new brand of Pemalang. “Pemalang pusere Jawa” has shown an impact on increasing tourism in Pemalang, Central Java, Indonesia. The Government supports the success of the City Branding program, and the people involved in the program, stakeholders, and culture, to boost tourism, which will have an impact on the economic sector and increase tourism significantly. Data were analyzed using the Exploratory Data Analysis (EDA) approach in qualitative research that defines and explains distribution characteristics. The data were collected through interviews with six key informants who were selected using a purposive sampling technique. Document studies were also conducted to support data analysis. This research uses the NVivo 12 Plus application to analyze data consisting of Concept Maps, Group Analysis, and Cluster Analysis. There are three points found in this study, consisting of 1) Program; the program is based on Pemalang Regent Regulation Number 27/2017 Article 7 concerning Utilization and Implementation of the City Branding Logo. The branding “Pemalang pusere Jawa” was launched in 2016 and the Visit Pemalang application is used to assist tourists in exploring tourism in Pemalang or known as a tour guide application. A Visit Pemalang application makes users easier to find tourism sites in Pemalang Regency by displaying the distance from the users’ location to the destination. 2) Partnership; this program is supported by infrastructure stakeholders consisting of the Planalogy Team, the Architect Team, and the Economic Development Expert Team. Program implementation involves the Government and the Community. 3) Culture; various annual events are held as an effort to preserve culture in Pemalang such as “Festival Wong Gunung” and other annual events. Community involvement in the implementation of City Branding is one of the success factors of the program.